-4(6-7x)=52

Question|Rated good

Asked 5/2/2012 10:14:27 AM

Updated 6/19/2014 8:02:46 AM

1 Answer/Comment

s

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Expert answered|lhyn29lhyn|Points 224|

Question|Rated good

Asked 5/2/2012 10:14:27 AM

Updated 6/19/2014 8:02:46 AM

1 Answer/Comment

Rating

8

-4(6 - 7x) = 52

-24 + 28x = 52

28x = 52 + 24 = 76

x = 76/28 = 19/7

-24 + 28x = 52

28x = 52 + 24 = 76

x = 76/28 = 19/7

Added 6/19/2014 8:02:46 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/19/2014 8:30:45 AM]

7(1 - q) = -3(5 + 3q) **Weegy:** 7(1 - q) = -3(5 + 3q) ;
7 - 7q = -15 - 9q ;
-7q + 9q = -15 - 7 ;
2q = -22 ;
q = -22/2 ;
q = -11 (More)

Question

Expert Answered

Updated 7/3/2018 9:47:20 AM

0 Answers/Comments

37 + 8q = 65 + 7q

Question

Not Answered

Updated 12/29/2017 3:08:38 PM

1 Answer/Comment

37 + 8q = 65 + 7q

8q - 7q = 65 - 37

q = 28

8q - 7q = 65 - 37

q = 28

Added 12/29/2017 3:08:38 PM

This answer has been confirmed as correct and helpful.

3.2-0.08w=-4 **Weegy:** Answer is w= 90
SOLUTION
-0.08w=-4-3.2; -0.08w=-7.2; w=-7.2/0.08; w=90 **User:** -0.5(0.3x-0.6)=-1.5 **User:** 4x+9+7x=31 **Weegy:** 4x+9+7x=31,
11x+9=31,
11x=31-9,
11x=22,
x=22/11,
x=2
**User:** -4(6-7x)=52 **Weegy:** -4(6-7x)=52,
-24+28x=52,
28x=52+24,
28x=76,
x=76/28,
x=2.714
(More)

Question

Expert Answered

Updated 8/18/2014 1:28:41 PM

1 Answer/Comment

The answer for -0.5(0.3x-0.6)=-1.5 is x=12.

-0.5(0.3x-0.6)=-1.5

-0.5*0.3x+0.5*0.6=-1.5

-0.15x+0.3=-1.5

-0.15x=-1.5-0.3

-0.15x=-1.8

0.15x=1.8

x=1.8/0.15

x=12.

-0.5(0.3x-0.6)=-1.5

-0.5*0.3x+0.5*0.6=-1.5

-0.15x+0.3=-1.5

-0.15x=-1.5-0.3

-0.15x=-1.8

0.15x=1.8

x=1.8/0.15

x=12.

Added 8/18/2014 6:00:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/18/2014 1:28:44 PM], Rated good by andrewpallarca

33,381,431

questions answered

There are no comments.